The Perspective of Millenial Tourists on Halal Tourism and itsReflection to Halal Tourism Development in West Sumatera - Pranita, Diaz; Kesa, Deni Danial (UI Scholars Hub, 2020)
As halal tourism demand show significant growth due to increase awareness of muslim tourists on consuming halal products and services during their travels, muslim millennials travelers becomes the most targeted market from destinations in the world, especially as they represent 25% of total tourism visitor arrivals. Therefore, this paper intends to reveal the perception of millennials on halal tourism and after that , the results to be projected in the development strategy of halal tourism in West Sumatera. It is an exploratory descriptive research in which primary data are collected through the distribution of questionnaire to 185 millennials in Jakarta. The results show that faith based needs especially the provision of halal food as well the opportunity to perform salaath and the availability of praying facilities along with water usage friendly washrooms are the most important services on their leisure travels. Muslim friendly accommodation, tourism attraction and shopping are the important facilities required, while the millennials search travel information and share their experience in social media. The most favorite tourism activities in halal tourism are adventure and family based tourism. To be successful in offering its halal tourism to millennials, West Sumatera should create its halal tourism products and services in accordance to the millennials tourists expectation.